2015
DOI: 10.1002/sia.5907
|View full text |Cite
|
Sign up to set email alerts
|

The role of acid‐base properties in the interactions across the oxide‐primer interface in aerospace applications

Abstract: In the transition to environmentally friendly production, chromic acid anodizing is being replaced by sulfuric acid, phosphoric acid or phosphoric-sulfuric acid anodizing. While it is known that using these acids leads to the incorporation of anions into the oxide, little is known on how they affect the nature of the oxide and how this, in turn, affects the interactions across the oxide-primer interface. In the current work, we investigate these changes in the interactions, especially the acid-base bonding, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
(55 reference statements)
2
11
1
Order By: Relevance
“…The spectra recorded from the front and the backsides of the sample are perfectly reproducible. The identification of the bands is based on comparison with the literature . Four bands are identified and discussed as follows: Band #1 with a maximum of between 940 and 960 cm −1 because of the Al‐O vibration mode and is commonly interpreted as typical for Al 2 O 3 fits well with earlier results of the authors …”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The spectra recorded from the front and the backsides of the sample are perfectly reproducible. The identification of the bands is based on comparison with the literature . Four bands are identified and discussed as follows: Band #1 with a maximum of between 940 and 960 cm −1 because of the Al‐O vibration mode and is commonly interpreted as typical for Al 2 O 3 fits well with earlier results of the authors …”
Section: Resultssupporting
confidence: 73%
“…The authors explain this band by the overlapping of the AlOH deformation vibration due to AlOOH (cf. 1060‐1070 cm −1 , 1060‐1070 cm −1 , and 1150 cm −1 ), and this is frequently interpreted as γ‐AlOOH or (pseudo‐) boehmite, and SO stretching vibration (cf. 1140, 1126, 1152, and 1130‐1190 cm −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…These are the same oxides that were formerly found to adsorb phenol molecules better than the other oxides, presumably due to the availability of weaker basic hydroxyl groups. Hence, the slight increase in peel strength after the transition from dry-to wet peel in here may be related to increased interfacial interactions in the presence of the weakly acidic phenols that are leached out of the resin in the presence of water to temporarily stabilize the interface 44 (since, as found earlier in Abrahami et al 24 , these reactions are reversible). This behavior has also been observed with other polymers including a study with poly(methyl methacrylate) (PMMA) polymer, Tannebaum et al 45 found that water helps to mediate bonding.…”
Section: Phenol-base Adhesive (Redux 775)supporting
confidence: 63%
“…Also, no distinction is seen between the part in the panel that was tested under dry-and wet conditions. Considering the chemical composition of Redux 775, adsorption to all substrates via alcohol and phenol groups present on the phenolic resole product can be expected according to our previous studies using model molecules 24 . In this study, the highest peel strengths were achieved with the hydrothermal, alkaline and CAA oxides.…”
Section: Phenol-base Adhesive (Redux 775)mentioning
confidence: 86%
See 1 more Smart Citation